Membaca Ulang Okinawa sebagai Entitas Budaya di Jepang: Komparasi Mitos Tanabata dan Tennyo no Ko - Habibi, Akbar Rizqi Dhea (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2025)
This study analyzes the Tanabata myth from mainland Japan and the Tennyo no Ko myth from Okinawa using Claude Levi-Strauss's structuralist approach. Through structural reading, binary oppositions such as upper–lower social groups are identified in the Tanabata myth, while the Tennyo no Ko myth reveals more complex oppositions, including upper–lower, public–private, and individual–communal. The Tanabata myth reflects Japanese cultural values that emphasize group exclusivity and the ie system. In contrast, Tennyo no Ko reflects Okinawan social structures oriented toward inclusivity, patrilineality, and communal connectedness. The analysis reveals that beneath the seemingly similar narrative structures lie fundamental differences in value systems and perspectives on social relationships. Accordingly, this study asserts that Okinawa possesses distinct social and cultural structures and should be understood as a culturally autonomous entity.